Application of metabolomics on marine sponges and sponge-associated microorganisms: A review - Putu Oka Samirana,, Riris Istighfari Jenie, Yosi Bayu Murti, Erna Prawita Setyowati (Journal of Applied Pharmaceutical Science, 2022)
Sponges and their associated microorganisms have tremendous potential in the medical world to be explored. However, improper exploration will cause habitat destruction and cost much. The application of metabolomics to sponges and their associted microbes can be the best solution in their exploration, which involves a combination of chemical profiling and multivariate analysis (chemometrics). In this , we 47 genera of sponges and 24 genera of their associated microorganisms that were studied with a metabolomic approach until July 2021. The sponges most often studied in metabolomics-related research are Geodia, Xestospongia, Agelas, and Aplysina. There are four analytical techniques that are often used, namely, liquid chromatography-mass spectrometry, polymerase chain reaction, nuclear magnetic resonance, and gas chromatography-mass spectrometry, in determining the chemical/genomic profile. There are eight chemometric analyses that are often used in metabolomic applications on sponges and their associated microbes, namely, similarity analysis, principal component analysis, hierarchical cluster analysis, partial least square, partial least square-discriminant analysis, orthogonal projections to latent structures, orthogonal projections to latent structures-discriminant analysis, and linear discriminant analysis. The most widely used metabolomic applications for sponges and their associated microbes for the last decade are for identification and dereplication purposes, for quality control purposes, and for the purpose of linking chemical profiles and bioactivity patterns. The purpose of other metabolomic applications, namely, to determine bioavailability to quantitatively determine bioactivity, and to test safety and toxicity, has yet to be carried out because research on sponges and their associated microbes is still around the discovery of new compounds and quality control.
Keywords: Metabolomics, sponge, associated microorganism, chemometrics, chemical profile